Battery-supported eCooking: A transformative opportunity for 2.6 billion people who still cook with biomass. (December 2021) - Leary, Jon; Leach, Matthew; Batchelor, Simon; Scott, Nigel; Brown, Ed
Abstract: Globally, 2.6 billion people still cook with biomass, resulting in interlinked health, environmental and drudgery challenges. The uptake of improved biomass cookstoves has barely kept up with population growth, yet SDG7 hopes for universal access to modern energy by 2030. This paper explores a potentially transformative new approach to facilitate access to affordable, reliable, sustainable and modern energy for cooking by leveraging rapid progress in electrification and falling prices of solar PV and lithium-ion batteries: battery-supported electric cooking. This paper presents empirical evidence on energy use, menu choices and cooking preferences from 83 households in 4 countries who transitioned from other fuels to electric cooking. A techno-economic model demonstrates that battery-supported electric cooking can be cost competitive with current expenditures on cooking fuels. No significant change in household menus occurred and the energy-efficient devices enabled 100% of everyday cooking with just 0.87–2.06 kWh/household/day. Our initial findings have already directly influenced the development of a 5-year UKAid-funded programme in collaboration with the World Bank, 'Modern Energy Cooking Services', and the new draft energy policy in Uganda. The paper concludes with two key policy recommendations: design lifeline tariffs inclusive of cooking and develop local markets for culturally-appropriate, quality-assured, energy-efficient cooking appliances. Highlights: Energy-efficient eCooking appliances are attractive to many households in LMICs. In LMICs, on-grid eCooking with efficient appliances is often cheaper than purchasing cooking fuels. Battery storage can mitigate concerns about peak loads and grid availability. Energy-efficient appliances enable cost-competitive battery-eCooking systems. Clean cooking can be enabled by policies leveraging rapid progress in electrification.